The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2110/palo.2015.031
|View full text |Cite
|
Sign up to set email alerts
|

A Marine Incursion In the Lower Pennsylvanian Tynemouth Creek Formation, Canada: Implications For Paleogeography, Stratigraphy and Paleoecology

Abstract: We document the occurrence of a marine bed, and its associated biota, in the Lower Pennsylvanian (Langsettian) Tynemouth Creek Formation of New Brunswick, and discuss its implications for paleogeography, stratigraphy and paleoecology. This is only the second marine interval found in the entire Pennsylvanian fill of the Maritimes Basin of Canada, the other being recently found in the broadly same-age Joggins Formation of Nova Scotia. Evidence for the new marine transgression comprises an echinoderm-rich limesto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
(84 reference statements)
2
4
0
Order By: Relevance
“…), whose salinity slowly decreased in a landward direction over many hundreds of kilometres (Falcon‐Lang ; Falcon‐Lang et al . ), similar to the present‐day Baltic Sea (Andersson et al . , ).…”
supporting
confidence: 75%
See 2 more Smart Citations
“…), whose salinity slowly decreased in a landward direction over many hundreds of kilometres (Falcon‐Lang ; Falcon‐Lang et al . ), similar to the present‐day Baltic Sea (Andersson et al . , ).…”
supporting
confidence: 75%
“…) and Tynemouth Creek (Falcon‐Lang et al . ) formations, and the new marine band (reported here) from the early to mid‐Bolsovian part of the Minto Formation. Colour online.…”
Section: Geological Contextsupporting
confidence: 54%
See 1 more Smart Citation
“…What is less certain is whether the burrows represent activity within freshwater tracts of the fluvial channels, or whether they are expressions of marine influence in the distal part of channel systems. The Tynemouth Creek Formation consists overwhelmingly of terrestrial red bed deposits, although a marine bed recently has been identified in the distal megafan (Falcon-Lang et al, 2016). Although Diplocraterion is characteristic of marine-influenced shoreface settings, the trace fossil also has been reported from freshwater fluvial channel tracts (Trewin and McNamara, 1994;Kim and Paik, 1997;Buatois and Mángano, 2004;Smith et al, 2012).…”
Section: Skolithos Ichnofaciesmentioning
confidence: 99%
“…The Lower Pennsylvanian (Bashkirian; Langsettian) Tynemouth Creek Formation conformably overlies the Boss Point Formation near Giffin Pond (Fig. 1C), and may be correlated (at least in part) with one or more of the Little River (Calder et al, 2005), Joggins (Davies et al, 2005) and Springhill Mines (Rygel et al, 2014) formations in the eastern part of the Cumberland Basin, and with the Lancaster Formation in the far western part of the basin (Falcon-Lang and Miller, 2007) based on biostratigraphy (Falcon-Lang et al, 2006Utting et al, 2011;Bashforth et al, 2014) and marine-based lithostratigraphy (Falcon-Lang et al, 2016) (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%